Clinical manual for treatment of alcoholism and addictions - Mack, Avram H.; Harrington, Amy L.; Frances, Richard J.; Mack, Avram H.; IG Publishing (Washington, DC American Psychiatric Pub., 2010)
The Clinical Manual for Treatment of Alcoholism and Addictions provides a concise overview of addiction treatment issues relevant to clinicians who are involved in the care of patients with substance use disorders.
Magnitude of the problem -- Neurobiology of addictive disorders and the disease concept -- Evaluation and assessment -- Definition, presentation, and diagnosis -- Natural histories of substance abuse -- Violence and suicide, injury, corrections, and forensics -- Behavioral addictions -- Children and adolescents -- Specific populations -- General hospital and primary care settings -- Treatment modalities -- Treatment approaches -- Public health issues.
Revision of: Concise guide to treatment of alcoholism and addictions / Avram H. Mack, John E. Franklin, Jr., Richard J. Frances. 2nd ed. c2001.
Electronic reproduction.
Keywords: Substance abuse -- Treatment -- Handbooks, manuals, etc; Alcoholism -- Treatment -- Handbooks, manuals, etc; Electronic books